The Combined Effects of Lee Silverman Voice Treatment and Abdominal Respiration on the Maximum Phonation Time in Parkinson's Disease - Byeon, Haewon (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose of the our study was to evaluate the effects of a respiratory rehabilitation the forced vital capacity, voice intensity, and maximum phonation time (MPT) of patients with hypokinetic dysarthria.Methods/Statistical analysis: This study was carried out on 32 patients with Parkinson's disease (PD). All subjects were randomly assigned to a treatment group (n = 17), which received both abdominal breathing training and LSVT, and a control group (n = 15), which only received abdominal breathing training. The forced expiratory volume at one second (FEV1) was measured in the sitting positing. The coordination of respiration and vocalization was measured by using MPT.Findings: The results of ANCOVA, which controlled the pre-test with a covariate, showed that the control group (CG) and the treatment group (TG) were significantly (p
Keywords: Lee Silverman Voice Treatment; abdominal breathing; LSVT; speech language pathology; Parkinson' disease; maximum phonation time; voice therapy